#TITLE_ALTERNATIVE# - KURNIA (NIM 12206082); Pembimbing: Prof. Pudji Permadi, M.Sc., Ph.D., IVAN
Permeability is one of the most important parameters in reservoir characterization and description. There are many correlations have been proposed and available in the petroleum literature. Unfortunately, these correlations were derived empirically without considering geological aspects. Rock typing is known to relate physical properties with geological characteristics of reservoir rocks. Therefore, rock typing should be important as the basis for predicting permeability. This paper presents the integration between engineering principles and geological aspect of core analysis data. The well known capillary tube model is the basis to generate the rock typing method. The geological core description data are used to characterize each of the generated rock types. This study employs 110 conventional and sidewall core samples of a sandstone reservoir. Results of this study demonstrate that rock types generated by the use of capillary tube model are consistent with the core description data in terms of the geological facies. The rock type equations derived from capillary tube model combined with capillary pressure data result in specific permeability equation for each rock type. Finally, the proposed method shows its superiority over previous correlations in predicting permeability.